Trabalho voluntário: relação entre motivação e cidadania em uma ONG ligada à educação na cidade de João Pessoa - PB - Maciel, Bárbara Stephanie Lira (2016)
The presente study had as subjects the active volunteers in an NGO linked to education in the city of João Pessoa-PB. It operates more than two years in São Rafael community and it has forty community volunteers, whom support this study, which aimed to know what are the motivations that contribute to the permanence and possible citizen attitudes of voluntary work of NGO studied. The theoretical models used were the one proposed by Cavalcante (2012) and the adapted questionnaire Citizen Audit, which allowed to identify the motivational profile and attitudes citizens of permanent volunteers. Data were collected through questionnaires applied during two group meetings and by e-mail contact, from July to September 2016. In the data analysis descriptive statistics were used (frequencies, percentages, averages, standard deviation and coefficient of variation) and the Pearson's correlation. As to the most significant results achieved there is the predominance of altruistic construct, followed by learning, social justice, membership and selfish. Regarding citizenship, many tend to have attitudes as citizens, how to see the importance of the government in the exercise of housing rights, labor and decrease the income gap between poor and rich. The altruistic construct obtained highest average and was that showed the most correlations whereas the learning had second highest average and showed only one correlation.